CARACTERIZACIÓN DE LA EVALUACIÓN EN EL PROCESO ENSEÑANZA-APRENDIZAJE EN LOS CURSOS DE QUÍMICA GENERAL DE LA EDUCACIÓN SUPERIOR. UNA APROXIMACION DESDE LA PERSPECTIVA DEL PROFESOR - Cabrera Morillo, Luz Marina; Castellanos Sánchez, Cheyron Eloína (Tecné, Episteme y Didaxis: TED, 2000)
ln order to have a transformation at the Teaching-Learning process in Colombian University Education, is necessary to change the conceptions about the process, the teacher and student actions in the classrooms, and the evaluations forms for application. Actually is developing a investigation to know the qualities of the students evaluation in a General Chemistry courses in Colombian Universities, developed by educational researchers at Universidad de Ciencias Aplicadas y Ambientales -U.D.C.A.-